Modeling the clarification of a suspension with the enhanced effect of the uncontrolled filtration rate on the interfacial mass transfer - Polyakov, V.L. (Reports of the National Academy of Sciences of Ukraine, 2018)
A mathematical task of the suspension purification on rapid filters with a storage device at the uncontrolled rate and a linear relation between the rate and mass exchange coefficients is formulated. An effective analytical numerical solution to the task is obtained to predict changes in filtration characteristics with regard for the hydraulic resistance of filter facilities, to substantiate rational technological parameters and, first of all, the filter cycle duration. The solution was illustrated by calculating the suspended substance concentration in a filtrate, filtration rate, and technological times.